Risk Management Analysis Based on ISO 31000:2018 at Andi Djemma Masamba Airport, Luwu Regency - Suriati Abd. Muin; Ade Apryanto A; Akbar Maulana (Faculty of Engineering, Andi Djemma University, 2024)
The density of activities that take place around the operating facilities at Andi Djemma Masamba Airport so that the Management of the Andi Jemma Airport Operator Unit (UPBU) Office has launched the development of Andi Djemma Masamba Airport as an aviation company so that it continues to carry out various facility improvements, especially in risk prevention with potential activities with high losses, therefore it is necessary to conduct research to find out how to map, risk assessment and design a risk control and mitigation system at the Operations facility at Andi Djemma Masamba Airport caused by activities that have the potential to cause risk. The stages of the risk management process refer to ISO 31000: 2018 including risk identification, risk analysis and risk evaluation. Expected impact and likelihood of occurrence are mapped through the risk matrix from the Federation Aviation Administration (FAA). The results showed that at the andi djemma masamba airport there were 6 events that fell into the red category, namely Aircraft accidents during take off/landing, Aircraft accidents in the apron area, Escape of dangerous goods into the aircraft, Fuel Spills on the Apron/Taxiway, Lack of building maintenance, The security inspection process is less than optimal.